Sistem Monitoring Kualitas Air Layak Pakai Menggunakan Arduino Uno - Ucmariance; Herdianto; Fery Anugrah; Chairul Rizal; Supiyandi (Bulletin of Information Technology (BIT), 2022)
In this design a tool is made to monitor the quality of water suitable for use using Arduino Uno. This design uses a pH meter sensor which functions to monitor acid levels in water and a turbidity sensor which is used to see the level of water turbidity. The use of these two sensors is based on the suitability of the water for consumption based on the acid level and the level of turbidity of the water. The results obtained in the design show that Arduino can read the acid levels in the water and see the level of turbidity of the water well so that the designed tools can be used directly to monitor the quality of water suitable for use.